Temperature reconstruction from 10 to 120 kyr b2k from the NGRIP ice core - P. Kindler; M. Guillevic; M. Baumgartner; J. Schwander; A. Landais; M. Leuenberger (Climate of the Past, 2014)
In order to reconstruct the temperature of the North Greenland Ice Core Project (NGRIP) site, new measurements of δ15N have been performed covering the time period from the beginning of the Holocene to Dansgaard–Oeschger (DO) event 8. Together with previously measured and mostly published δ15N data, we present for the first time a NGRIP temperature reconstruction for the whole last glacial period from 10 to 120 kyr b2k (thousand years before 2000 AD) including every DO event based on δ15N isotope measurements combined with a firn densification and heat diffusion model. The detected temperature rises at the onset of DO events range from 5 °C (DO 25) up to 16.5 °C (DO 11) with an uncertainty of ±3 °C. To bring measured and modelled data into agreement, we had to reduce the accumulation rate given by the NGRIP ss09sea06bm timescale in some periods by 30 to 35%, especially during the last glacial maximum. A comparison between reconstructed temperature and δ18Oice data confirms that the isotopic composition of the stadial was strongly influenced by seasonality. We evidence an anticorrelation between the variations of the δ18Oice sensitivity to temperature (referred to as α) and obliquity in agreement with a simple Rayleigh distillation model. Finally, we suggest that α might be influenced by the Northern Hemisphere ice sheet volume.